Studi komparasi pemikiran Imam Syafi’i dan Imam Hanafi tentang wali mujbir - Agus , Nina; Chaosa, Vreede Intang (AS-SAKINAH, 2023)
Imam Shafi'i stated that as long as the daughter still has the status of al-bikr (girl) then the right of a guardian still exists, the limit of al-bikr (girl) according to Imam Shafi'i is that as long as the woman has never had sex (jima'), even though she has sex by adultery then the person is not punished by al-bikr (girl) anymore, this statement of Imam Shafi'i includes a girl who is divorced by her husband but has never been (qobla dukhul), because in essence the woman still has the status of al-bikr (girl) Researchers use data collection methods with documentation techniques. After obtaining the necessary data, then the data is analyzed by comparative analysis methods. With the comparative study of the opinions and methods of legal istinbat used by Imam Hanafi and Imam Shafi'i about wali mujbir. The methods of istinbat wali mujbir used by Imam Shafi'i are the Qur'an, sunnah and qiyas, while the legal istinbat methodsused by Imam Hanafi in the matter of wali mujbir are the Qur'an, sunnah and 'Urf. The Illat used by Imam Shafi'i is bikr (virginity), while the Illat used by Imam Hanafi in the concept of ijbar guardianship is ghairu aqilah. Because the woman in those circumstances is incapable of acting something for herself.